Correction of skin condition and homeostasis of the body in employed men by the courses of vitamin therapy - N. Yu. Reznichenko (Zaporozhye State Medical University, 2014)
There has been deterioration in the health of men of working age in recent years. Aim.To study the effectiveness of prophylactic use of multivitamins and the combined use of biotin and dexpanthenol among employed men aged 35-44 years. Methods and results. 128 persons have been examined by means of questionnaires, clinical examination, biochemical studies. Clinical and biochemical efficacy of preventive courses of vitamins has been established. Conclusion.The obtained data indicate the need for wide use of vitamin prophylaxis to maintain health in men aged 35-44 years